ANALISIS PENGENDALIAN PERSEDIAAN MENGGUNAKAN PENDEKATAN MUSIC 3D ( MULTI UNIT SPARES INVENTORY CONTROL- THREE DIMENSIONAL APPROACH) PADA WAREHOUSE DI PT SEMEN INDONESIA (PERSERO) TBK PABRIK TUBAN - Dian Janari; Manzula Maulida Rahman; Adhe Rizky Anugerah (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Inventory control is a process that is vital to the company's operations, with the aim to prevent the company from stock-outs and to keep costs as optimally as possible to the activities related to the provision. PT. Semen Indonesia as a national cement company in Indonesia has a problem in controlling inventory, including inventory value that exceeds the target, the value of deadstock which reached Rp. 80,000,000, and the number of items that reached 52,700 items. MUSIC 3D method is an approach that can overcome the problems of inventory control in PT. Semen Indonesia. This method is a theory to group items based on several aspects. In this study, only three elements in MUSIC 3D are applied, which are ABC analysis (value based), SDE (lead time), and FSN (consumption rate) with the sample as many as 990 types of goods. The results show that the type of CDN products is goods that dominate in the warehouse of PT. Semen Indonesia, with the following characteristics: C (low price with the high volume of quantity), D (lead time <6 months) and N (not used <1 year) with the percentage reached 32% from the total quantity in the warehouse of PT. Semen Indonesia.